The Impact of Budget Participation towards Managerial Performance: Job Satisfaction and Perception of Innovation as the Intervening Variables (A Case Study for the Regional District Organization (OPD), Districts of Kudus) - Nanik Ermawati; Diah Ayu Susanti; Zamrud Mirah Delima (President University Press, 2018)
The preparation of the budget for the Regional District Organization (OPD) of the Kudus Regency adopted a budget participation model that involved OPD employees from the head of the OPD to the staff. With the involvement of OPD employees in preparing this budget, it can provide improved managerial performance of OPD employees in their work. But there are several other factors that can improve performance, including job satisfaction and perception of innovation. Therefore in this study will be explained the effect of budget participation on managerial performance through the perception of innovation and job satisfaction as an intervening variable in the regional device organization in Kudus Regency. This research was conducted by questionnaire method through data collection techniques by giving a set of questions to respondents. Questionnaires were given to OPD employees consisting of heads of regional apparatus organizations, field heads, section heads and staff. The test tool used in this study is Path path analysis. The results showed that budgetary participation, job satisfaction, innovation perception had an effect on managerial performance, budget participation had an effect on job satisfaction and perceptions of innovation, but job satisfaction and innovation perception were not able to mediate the influence of budget participation on managerial performance.